Paths Towards Multispecies Superintelligence and Socio-Economic Justice: Nicoletta Vallorani’s Il Cuore Finto di DR - Eleanor Drage (Fafnir, 2020)
This paper examines how non-unitary, responsive, and multispecies superintelligence can create an economic model that upends systems of race and gender in Nicoletta Vallorani’s Il Cuore Finto di DR. The novel depicts a dynamic slum ecosystem that sustains the lives and livelihoods of an array of human and non-human critters. At the heart of the slum economy is a Replicant-in-hiding called DR, whose gender- and species-destabilising body is evocative of Donna Haraway’s boundary creatures: she is an adaptive, inter-relational critter who bypasses traditional gendered markers of economic value and demonstrates a responsiveness to the needs of her community. Faithful to the multiple genealogies of humanistic Italian science fiction, Il Cuore Finto examines how adaptive superintelligent affiliations can transform not only the economy, but also the systems of race and gender that dictate which lives are valued in an unerring system of capital accumulation.